The Effectiveness of Augmented Reality As Learning Media For Students With Intellectual Disabilities Intellectual Disabilities - Afif, Elma Fatikha; Agustina, Ulfa Wulan; Afidah, Nurul; Bachtiar, Yuyun (SALIENCE: English Language, Literature, and Education Journal, 2025)
The purpose of this research is to ascertain whether Augmented Reality (AR) is a useful learning tool for helping students with intellectual disabilities recognize animal names and whether a rise in the average score of these students occurs. A new technology that mixes two- and three-dimensional items with information in a true projection is called Augmented Reality (AR). We employed pre-experimental design and experimental research approaches in this work. As tools for gathering data, the researcher performed tests and observations twice at each meeting. According to SLB Muhammadiyah Jombang research, Augmented Reality (AR) significantly enhances learning for students with intellectual disabilities, particularly when it comes to identifying animal names. Following the use of Augmented Reality (AR), the average pre-test score rose to 73.87, while the post-test score rose to 88.50. High levels of involvement and enthusiasm were evident during the Augmented Reality (AR) lecture, according to observation results. Augmented Reality (AR) has a good influence on student attention and engagement, as evidenced by the N-Gain formula's effectiveness score of 64.06%. For students with intellectual disabilities, Augmented Reality (AR) is a useful tool to improve their educational experience.